2009
DOI: 10.1186/1755-8794-2-59
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression meta-analysis supports existence of molecular apocrine breast cancer with a role for androgen receptor and implies interactions with ErbB family

Abstract: BackgroundPathway discovery from gene expression data can provide important insight into the relationship between signaling networks and cancer biology. Oncogenic signaling pathways are commonly inferred by comparison with signatures derived from cell lines. We use the Molecular Apocrine subtype of breast cancer to demonstrate our ability to infer pathways directly from patients' gene expression data with pattern analysis algorithms.MethodsWe combine data from two studies that propose the existence of the Mole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
40
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(41 citation statements)
references
References 60 publications
1
40
0
Order By: Relevance
“…Androgens also enhance activation of ERK, a downstream effector of HER2, and HER2-AR crosstalk is required for proliferation and viability of molecular apocrine breast cancer cell lines (Naderi & Hughes-Davies 2008, a concept that is supported by bioinformatic analysis of gene expression profiles in molecular apocrine breast cancer tissues (Sanga et al 2009). This reveals that AR and FOXA1 utilise a complex regulatory network to enhance the tumourigenic potential of breast cancer cells, at least in a molecular apocrine context.…”
Section: Ar Foxa1 and Her2mentioning
confidence: 99%
“…Androgens also enhance activation of ERK, a downstream effector of HER2, and HER2-AR crosstalk is required for proliferation and viability of molecular apocrine breast cancer cell lines (Naderi & Hughes-Davies 2008, a concept that is supported by bioinformatic analysis of gene expression profiles in molecular apocrine breast cancer tissues (Sanga et al 2009). This reveals that AR and FOXA1 utilise a complex regulatory network to enhance the tumourigenic potential of breast cancer cells, at least in a molecular apocrine context.…”
Section: Ar Foxa1 and Her2mentioning
confidence: 99%
“…[13][14][15][16] This molecular apocrine group was characterized by increased AR signaling along with increased human epidermal growth factor receptor 2 (HER-2)/neu gene signaling. 13,16 A study using an apocrine cell line model also demonstrated the existence of a functionally significant cross-talk between AR and HER-2/neu pathways through ERK1/2 in ER-negative breast carcinomas. 17 This cross-talk affects cell proliferation and apoptosis and could have a significant therapeutic impact.…”
mentioning
confidence: 99%
“…33 A ''normal breast-like'' subtype has been identified, but its existence has been questioned on the grounds that many of the normal breast-like tumors have been paucicellular and therefore have consisted mainly of nontumor tissue, 33 which of course, upon expression profiling, resembled normal breast. Rare intrinsic subtypes include claudin-low, with low expression of cell adhesion genes, 34 and molecular apocrine-like, 35 which often expresses androgen receptors. 36 …”
Section: Basis Of Testmentioning
confidence: 99%